Дом на краю ночи: [роман] / Кэтрин Бэннер - Бэннер Кэтрин (Фантом Пресс, 2018)
Экземпляры: ф.8 (20201026) / Инвентарный номер: 60370 / Цена: / Сис.шифр: 84(4Вел)-4 / Авт.знак: Б 975 / ГРНТИ: 17.82.31 / ББК: 84(4Вел)-44